FIRM VALUE OF THE PROPERTY, REAL ESTATE & BUILDING SECTOR IN INDONESIA AT THE BEGINNING OF THE COVID-19 PANDEMIC - Kusuma, Indah; Santhi, Rayhita; Putra, Cahyadi (International Journal of Application on Economics and Business, 2023)
Movements in Indonesian stocks through the Composite Stock Price Index (IHSG) in 2020 experienced great turmoil as a result of the Corona Virus Diseases-19 (Covid-19). The data shows that the value of companies listed on the Indonesia Stock Exchange (IDX) is not in its best condition. This study uses an associative quantitative approach to examine 38 listed issuers in the property, real estate & building sector during 2020. The results of this study are able to prove that the firm value during the current pandemic is influenced by financial distress.